The Impact Of Service Quality & Dining Atmosphere Towards Customer Satisfaction At Authentic Restaurants In Tangerang - Goeltom, Vasco Adato H.; Juliana , Juliana; Angelina , Jacklyn; Tandra , Jane Keisya; Valencia, Vallery; Sianipar, Rosianna (SEAN Institute, 2024)
This study aims to test and analyze the effect of Service Quality and Dining Atmosphere on Customer Satisfaction at Authentic Restaurants in Tangerang. The sampling technique in this study includes non-probability sampling where the sampling in this study is not random and is aimed specifically at the population specifically at customers who have visited one of the three Authentic Restaurants in Tangerang. This study took a sample of 157 respondents. The method applied in this research is descriptive quantitative method, and the data collected from respondents is analyzed using the SmartPLS application The results in this study show that: (1) Service Quality has a positive effect on Customer Satisfaction, (2) Dining Atmosphere has a positive effect on Customer Satisfaction.